Depositional Environment and Stratigraphic Evolution of Hartha Formation in Balad and East Baghdad Oil Fields, Central Iraq - Ismail, Aliya Sadoon; Nasser, Midhat E.; Al-Sharaa, Ghazi H. (Iraqi Journal of Science, 2022)
Five subsurface sections and a large number of thin sections of the Hartha Formation (age Late Campanian – Early Maastrichtian) were studied to unravel the depositional facies and environments. The Hartha Formation is important as an oil reservoir in Iraq.Petrographic and microfacies analysis of selected wells from Balad and East Baghdad oil fields in Central Iraq, enable the recognition of three main Sedimentary paleoenvironments. These are restricted marine, the shallow open marine environment within the inner ramp, deep outer ramp.The studied Formation represents by two asymmetrical cycles bounded below by sequence boundary (SB1) the contact between Hartha and Saadi Formations. The deep outer ramp facies of the transgressive systems tract continue with the lower part of the Hartha Formation. Two depositional sequences consist of transgressive system tract and high stand system tract, separated by maximum flooding surface. These happened and represented the transgressive systems tract of the cycle that continues until the Shiranish Formation, which overlies the Hartha Formation.